MODULATORY ROLE OF N-ACETYL-CYSTEINE ON GASTRIC MUCOSAL LESION AND HAEMATO-BIOCHEMICAL CHANGES IN ALBINO WISTAR RATS SUBJECTED TO INDOMETHACIN TREATMENT - SADAU, Y; MUHAMMAD, M.S; LAI, I, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2021)
Gastric ulcer is caused by multifaceted etiological factors such as environmental and indiscriminate use of non-steroidal anti-inflammatory drugs (NSAIDs) such as Indomethacin. N-acetyl-cysteine (NAC) is an antioxidant that protects the lipid biomembrane against oxidative stress. This study investigated the effect of NAC on gastric mucosal lesion and haemato-biochemical changes in albino Wistar rats subjected to indomethacin treatment. Twenty (20) adult male rats, were divided into five (5) groups; Group I (Control): Were administered with distilled water/kg/Bdw, Group II: Indomethacin 40 mg/kg in 0.5 % carboxymethylcellulose (Ulcer group), Group III: Received 2.5 ml/kg of 0.5% CMC, Group IV: Received NAC 500 mg/kg/Bdw orally + Indomethacin (500 mg/kg), Group V: Received Ranitidine 50 mg/kg/Bdw + Indomethacin (40 mg/kg). All treatment lasted for 7 days. Three hours after last treatment, rats were humanely sacrificed. The stomach and blood samples were collected for physical and biochemical analysis. Data was analysed using ANOVA and p < 0.05 was considered significant. The P index of NAC in indomethacin induced ulcer is found to be 75 %. A significant increase (p < 0.05) in final body weight was observed in Indomethacin group, when compared to the control, CMC and Ranitidine + Indomethacin groups. A significant (p < 0.05) increase in inducible nitric oxide synthase (INOS) concentration was observed in all treatment group, when compared to the control. In conclusion, we surmise that acute administration of Indomethacin increased body weight of rats, which was decreased by CMC and Ranitidine treatments, while NAC treatment failed to improve haematobiochemical changes in adult Wister rats.